ASPEK HUKUM PIDANA PENAGIHAN UTANG PINJAMAN Online ILEGAL OLEH Desk collector YANG MENYEBARKAN KONTEN PORNOGRAFI BERDASARKAN UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Wening Novridasati; Armansyah (Jurnal Hukum dan Bisnis (Selisik), 2022)
There a lot of illegal fintech applications that are unsettling, the desk collector uses methods to collect the debt by abusive, tend to be threatening, inhumane, and contrary to the law, causing victims whose impacts can be felt both psychologically and physically, or contain moral content that spread pornography content , there were some victims who were ended their lives, and victims did not get their rights. The problems examined is the criminal liability desk collectors illegal online loans in collecting debt according to the Electronic Information and Transaction Law, and regarding protection against victims of illegal online loan collection contain moral content. This research used a normative juridical method with statutory approachment. The data sources used in this study are secondary data that analyzed qualitatively. The results obtained by this research are that the acts carried out by the desk collector in collecting debts violate the Article 27 Paragraph (1) of The Electronic Information and Transaction Law, besides that both of them can be asked for criminal liability using strict liability patterns which is charged to the desk collector and can also use the vicarious liability pattern which is charged to the company management (directors), but the form of criminal liability is only borne by the desk collector individually. And victims entitled to get restitution as a form of protection against victims of illegal online loan collection, but the victim was only a witness in the real and did not receive the victim’s right